Role of Community Leaders as Motivator in Waste-Bank Management in Magetan Regency, Indonesia - Retananda Ragiliawati; Mochammad Bagus Qomaruddin (Universitas Airlangga, 2020)
Background: Garbage is one of the unsolved problems in Indonesia. Riskesdas data for 2018 show that 63.2% of the quality of household waste management in Indonesia is in a bad category. The landfill site in Magetan Regency is currently overloaded. The waste bank is an alternative solution for solving problems. Tawanganom Village, Magetan District, Magetan Regency, won the Regency Level Healthy Village Competition in 2017 with fifth community association (RW 5) as the competition representative because it fulfilled the criteria of the championship, namely the existence of a waste bank. It is inseparable from the active role and social support of community leaders who motivate the community to participate in waste bank management. Objectives: Describe the role of community leaders as motivators in supporting waste bank management, including emotional support, appreciation, instrumental, and information. Methods: The method used in this research is qualitative with a case study approach. In-depth interviews were conducted with informants consisting of housewives and community leaders involved in waste bank activities. The determination of informants was carried out purposively with in-depth interviews using an interview guide. Results: It shows that the role of community leaders as motivators significantly affects the sustainability of the waste bank in RW 5, Tawanganom Village, Magetan Regency. Community leaders show patience in guiding the community, providing appreciation and various rewards so that the community feels proud and appreciated, and enables the community to move independently in managing the waste bank. Conclusion: The role of community leaders as motivators impacts increasing community participation in waste bank management. The waste bank can run smoothly, supported by the attention and concern of the local government and community leaders who are aggressively providing information and suggestions related to waste bank management.